Life Science 2.0: reframing the life science sector for ‘the benefit on mankind’ - Michaela Vallin; Göran Tomson; Beate Kampmann; Eivind Engebretsen; Stefan Swartling Peterson; Rhoda K. Wanyenze; Ole Petter Ottersen (Global Health Action)
The COVID-19 pandemic put the life science sector to the test. Vaccines were developed at unprecedented speed, benefiting from decades of fundamental research and now honoured by a Nobel Prize. However, we saw that the fruits of science were inequitably distributed. Most low- and middle-income countries were left behind, deepening the inequalities that the Sustainable Development Goals were set to reduce. We argue that the life science sector must reinvent itself to be better and more equitably prepared for the next health crisis and to ensure fair access to health across current and future generations. Our recommendations include global governance, national strategies and the role of universities and corporations. Improved and more equitable health care should be centre stage for global health action and a core mission of a reframed Life Science sector – what we call Life Science 2.0. Paper Context Main findings: During the COVID-19 pandemic the Life Science sector stepped up to the challenge, but vaccines and medicines were not equitably distributed. Added knowledge: Obstacles were identified that hindered global access to medical innovations. Global health impact for policy and action: Global and national governance, universities and the private sector should join forces to create a Life Science sector (Life Science 2.0) that affords equitable access to medical advances across geographical and generational boundaries and socio-economic strata.